2015
DOI: 10.1073/pnas.1515954112
|View full text |Cite
|
Sign up to set email alerts
|

Beta cells transfer vesicles containing insulin to phagocytes for presentation to T cells

Abstract: Beta cells from nondiabetic mice transfer secretory vesicles to phagocytic cells. The passage was shown in culture studies where the transfer was probed with CD4 T cells reactive to insulin peptides. Two sets of vesicles were transferred, one containing insulin and another containing catabolites of insulin. The passage required live beta cells in a close cell contact interaction with the phagocytes. It was increased by high glucose concentration and required mobilization of intracellular Ca 2+ . Live images of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 42 publications
5
95
0
1
Order By: Relevance
“…However, the mechanism leading to this delayed antibody response was not investigated in this study (Satoh et al 2011). A recent elegant publication showed that β-cells transfer antigenic epitopes to antigen presenting cells via a direct membrane contact (Vomund et al 2015). This is a novel mechanism, however, not specific for 'diabetic' β-cells, since it was observed in both diabetic and nondiabetic mice and in nondiabetic humans.…”
Section: Er Stress and Antigen Presentationmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the mechanism leading to this delayed antibody response was not investigated in this study (Satoh et al 2011). A recent elegant publication showed that β-cells transfer antigenic epitopes to antigen presenting cells via a direct membrane contact (Vomund et al 2015). This is a novel mechanism, however, not specific for 'diabetic' β-cells, since it was observed in both diabetic and nondiabetic mice and in nondiabetic humans.…”
Section: Er Stress and Antigen Presentationmentioning
confidence: 87%
“…This is a novel mechanism, however, not specific for 'diabetic' β-cells, since it was observed in both diabetic and nondiabetic mice and in nondiabetic humans. Interestingly, high glucose increased the transfer of epitopes (Vomund et al 2015). The mechanism for this increase has not been yet investigated, but it would be interesting to verify whether it is not due to high glucose-induced ER stress.…”
Section: Er Stress and Antigen Presentationmentioning
confidence: 99%
“…Like other resident macrophages, islet macrophages are also likely to be important in phagocytosing dead or dying cells and debris and maintaining islet cell homeostasis. Islet macrophages continuously sample antigen from beta cells [17] and, through surveying the blood vessels and islet milieu for danger signals and invading pathogens, also act as an important first line of immunological defence. Mice lacking tissue resident macrophages have reduced beta cell mass [18] and, more recently, macrophages have been found to play an important role in beta cell proliferation and regeneration in models of acute beta cell loss [19][20][21].…”
Section: Islet Macrophages In Health and Diseasementioning
confidence: 99%
“…Evidence exists for chronic beta cell-derived cues that macrophages respond to, including the accumulation of IAPP aggregates in type 2 diabetes, which induce a robust inflammatory response [8,9,12]. Intriguingly, intact insulin granules have also been observed within islet macrophages, indicative of an intimate interaction between these cell types [17].…”
Section: Beta Cell-islet Macrophage Crosstalkmentioning
confidence: 99%
“…Although insulin is by far the major secreted product of primary beta cells, this cell type likely expresses hundreds of other secreted proteins [52], several of which have known physiological roles [52][53][54]. Future studies should also address the completeness of insulin processing, as it is possible that improperly processed and/or secreted insulin can provoke or accelerate beta cell directed autoimmunity [55].…”
Section: Remaining Obstacles-deep Phenotypingmentioning
confidence: 99%